2010
DOI: 10.1038/aja.2009.97
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of SK3 and IK1 channel proteins in the cavernous tissue of diabetic rats

Abstract: The small (SK3) and intermediate (IK1) conductance calcium-activated potassium channels could have key roles in the endothelium-dependent hyperpolarization factor pathway, which is believed to contribute to normal penile erection function. We aimed to investigate the expression of SK3 and IK1 in diabetic rodents. The experimental diabetes model was induced in 8-week-old male Sprague-Dawley rats (250-300 g) by a single administration of streptozotocin. Both the diabetes mellitus group (DM group, n = 20) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…A reduced expression level of SK Ca and IK Ca associated to blunted EDHF-mediated relaxations has also been observed in the rat mesenteric artery following angiotensin II-induced hypertension [30] or common bile duct ligation [24], and in the rat cavernous tissue following streptozotocin-induced diabetes [31]. The present findings suggest that the beneficial effect of the RWPs treatment on the EDHF component might be due, at least in part, to their ability to restore the expression of SK Ca and IK Ca to a level similar to that observed in young adults.…”
Section: Discussionmentioning
confidence: 79%
“…A reduced expression level of SK Ca and IK Ca associated to blunted EDHF-mediated relaxations has also been observed in the rat mesenteric artery following angiotensin II-induced hypertension [30] or common bile duct ligation [24], and in the rat cavernous tissue following streptozotocin-induced diabetes [31]. The present findings suggest that the beneficial effect of the RWPs treatment on the EDHF component might be due, at least in part, to their ability to restore the expression of SK Ca and IK Ca to a level similar to that observed in young adults.…”
Section: Discussionmentioning
confidence: 79%
“…Diabetic neuropathy in mice is accompanied by glycocalyx alteration in brain microvessels (49). Finally, diabetes significantly reduces EDHmediated vasorelaxation in human penile resistance arteries and downregulates SK3 and IK1 channels in rat corpus cavernosum tissues (32). HYAL1 inhibition could thus be a first step to prevent loss of glycocalyx during the development of diabetic nephropathy, retinal microangiopathy, blood-brain barrier damage, and erectile dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that diabetes mellitus alters the aromatase enzyme in the gonadal tissues of rats, which may result into the induction of reproductive dysfunction (Burul-Bozkurt et al 2010). Diabetes inhibits mRNA and protein expression of both small (SK3) and intermediate (IK) conductance calcium-activated potassium channels in the cavernous tissue of diabetic rats, which could play a key role in the development of erectile dysfunction in diabetic rats (Zhu et al 2010). There are several reports in the literature that babies born to type I diabetic mothers are having altered growth and body composition, skeletal deformities as well as other abnormalities (Mughal et al 2010;Eidem et al 2010).…”
Section: Introductionmentioning
confidence: 97%